Police officers - Ready, Dee. (Mankato, Minn. : Bridgestone Books, 1997)
Explains the clothing, tools, schooling, and work of police officers.
Includes bibliographical references (p. 24) and index.
Keywords: Police -- United States -- Juvenile literature; Police; Occupations